The Impact of Digital Transformation in the Accounting System of Fuel and Energy Complex Enterprises (International Experience) - Zakharkina, Liudmyla; Rubanov, Pavlo; Alibekova, Balsheker; Zakharkin, Oleksii; Moldashbayeva, Luiza (International Journal of Energy Economics and Policy, 2022)
The global fuel and energy market occupies a significant position in international trade, which encourages companies in the industry to carry out a digital transformation in the supply chain and accounting of related transactions. Digital transformation occurs through the introduction of modern information technology, which leads to increased productivity at all stages of the supply chain in the fuel and energy sector and simplified accounting of transactions. Positive processes are characterized by the convergence of markets, and negative processes are characterized by the fragmentation of energy markets and their isolation at the national level. To solve these problems in the field of accounting, it is necessary to constantly improve ERP systems based on the creation of a unified ecosystem of the fuel and energy sector. The world practice of using Enterprise Resource Planning products in the fuel and energy sector is considered. Based on the trend and structural analysis world oil and gas imports have been investigated to determine the dynamics and geographical structure of the fuel and energy market. The forecast of the dynamics of oil imports is made. The article proposes a functional model of the supply chain in the energy sector based on blockchain technology. The article defines digital technology with a focus on blockchain and artificial intelligence. The process method is used in the formation of an invoice generation model. The advantages of ERP systems are identified and global experience in invoice generation in accounting is summarized. The OpenText Vendor Invoice Management (VIM) software product is characterized, allowing its integration with the SAP ERP invoice accounting and payment system. The main issues of digital transformation in the accounting system, stimulating the improvement of specialists’ competencies when working with digital platforms, are identified.